2006
DOI: 10.1590/s0100-879x2006001100009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pentoxifylline on lung inflammation and gas exchange in a sepsis-induced acute lung injury model

Abstract: Experimental models of sepsis-induced pulmonary alterations are important for the study of pathogenesis and for potential intervention therapies. The objective of the present study was to characterize lung dysfunction (low PaO 2 and high PaCO 2 , and increased cellular infiltration, protein extravasation, and malondialdehyde (MDA) production assessed in bronchoalveolar lavage) in a sepsis model consisting of intraperitoneal (ip) injection of Escherichia coli and the protective effects of pentoxifylline (PTX). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
14
0
4
Order By: Relevance
“…19 Modulation of IL-10 mRNA expression was much less pronounced than that of TNF-a. In contrast to TNF-a, a constitutive expression of IL-10 mRNA was found in control animals, with only moderate modulation along the 28 days of the experiment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…19 Modulation of IL-10 mRNA expression was much less pronounced than that of TNF-a. In contrast to TNF-a, a constitutive expression of IL-10 mRNA was found in control animals, with only moderate modulation along the 28 days of the experiment.…”
Section: Discussionmentioning
confidence: 97%
“…18 We have previously shown that TNF-a and IL-6 were detected in high levels of bronchoalveolar lavage (BAL) in rats injected intraperitoneally with Escherichia coli . 19 In this study we aimed to evaluate the expression of tissue TNF-a, IL-10, and endothelial nitric-oxide synthesis (eNOS) mRNA levels in an experimental model of Leptospirainduced lung dysfunction, assessed by functional and histologic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Em nosso meio, desenvolvemos um modelo de disfunção pulmonar, com foco infeccioso , que tem mostrado relevância clÍnica no estudo das doenças, tendo ainda a possibilidade de se testar intervenções terapêuticas. Nesse modelo, demonstramos que a pentoxifilina (PTX) reduz as proteínas totais no lavado broncoalveolar de animais sedados e em respiração espontâ-nea, submetidos a infusão intraperitoneal de Escherichia coli (E. coli) 21 . O presente estudo teve como objetivo avaliar as alterações bioquímicas e morfométricas no pulmão de ratos com disfunção pulmonar induzida por sepse e suporte ventilatório tratados com pentoxifilina.…”
Section: Introductionunclassified
“…O presente estudo teve como objetivo avaliar as alterações bioquímicas e morfométricas no pulmão de ratos com disfunção pulmonar induzida por sepse e suporte ventilatório tratados com pentoxifilina. 21 . Consiste na administração intraperitoneal de 1mL/100g de peso corporal (1 mL corresponde a 10 7 unidades formadoras de colônia -UFC), de uma solução de bactérias, essas bactérias foram classificadas pela bioquímica e morfologia como Escherichia coli R-6.…”
Section: Introductionunclassified
“…Plasma and BAL levels of MDA have been shown to increase significantly in experimental studies of acute lung injury (21,22). Septic lung injury models in rats showed the increase in lung tissue MDA levels which decreased after application of N-acetylsistein or methylene blue (18,23).…”
mentioning
confidence: 99%